Interference of the Political Class in Public Senior Secondary School Leadership in Rivers Southeast Senatorial District of Rivers State.: EDUCATIONAL MANAGEMENT - Clifford Bariton Nwisane (International Journal of Educational Management and Innovation, 2023)
This study focuses on the Interference of the Political Class in Public Senior Secondary School Leadership in Rivers southeast Senatorial District of Rivers State. The study adopted a Descriptive research design. The population comprised 234 respondents (78 Principals, 78 Vice Principal Administration, and 78 Academics. Census was used to select the population. The questionnaire was used for data collection. The reliability of the instrument was obtained using test-retest method statistics. Twenty senior secondary school principals were administered the questionnaire, and a reliability index of 0.739 and 0.81 was obtained through Pearson Product Moment Correlation statistics. Mean and standard deviation was used to answer research questions 1-4, while an independent t-test was used to test the hypotheses at a 0.05 alpha significance level. The findings showed no significant difference between the mean ratings of principals and vice principals in the interference of politics on the appointment, promotion, posting of staff personnel, etc. From the findings, the study concludes that government should come up with acceptable criteria for appointing principals to ensure proper management of the schools, and the government should support the in-service training of staff to ensure teacher competency.